2014
DOI: 10.1111/j.1948-7134.2014.12086.x
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition byAedes aegyptiandAedes albopictus: Influence of congeners and of oviposition site characteristics

Abstract: We investigated the oviposition behavior of Ae. aegypti and Ae. albopictus. In particular we examined whether small-scale site characteristics and the presence of conspecifics or congeners altered oviposition by these mosquitoes. Various combinations of females of the two species were allowed to oviposit inside cages among either vegetation (potted plants) or structural components (wood and concrete blocks). Numbers of eggs deposited per female were compared between species, sides, and treatments. Most signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 37 publications
(46 reference statements)
3
27
0
2
Order By: Relevance
“…Since 2011, Ae. albopictus has been found in all of Managua's municipalities (Table 1); however, our detailed entomological surveys in 2012 demonstrated greatest abundance in peripheral neighborhoods of the city of Managua with semiurban conditions, consistent with previous reports (Rey and O'Connel 2014). This evidence for the movement and invasion of Ae.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Since 2011, Ae. albopictus has been found in all of Managua's municipalities (Table 1); however, our detailed entomological surveys in 2012 demonstrated greatest abundance in peripheral neighborhoods of the city of Managua with semiurban conditions, consistent with previous reports (Rey and O'Connel 2014). This evidence for the movement and invasion of Ae.…”
Section: Discussionsupporting
confidence: 90%
“…While Ae. albopictus is more ubiquitous in natural breeding sites, its immature forms can cohabit and compete with other container-breeding mosquitoes (Rey and O'Connel 2014).…”
Section: Discussionmentioning
confidence: 99%
“…aegypti between sewage water and clean water, and found that females had no preference for oviposition choice or and experienced no difference in oviposition success between sewage water and clean water. Williges et al [34] and Rey and O’Connell [35] also studied oviposition site characteristic preferences. Williges et al [34] studied oviposition height preference, and found that Ae.…”
Section: Resultsmentioning
confidence: 99%
“…albopictus preferred to oviposit at ground level, compared to 1, 2, 3 or 4m in height under semi-field conditions. Rey and O’Connell [35] studied vegetation vs. structural component (wood and concrete blocks) oviposition site preference among Ae. aegypti and Ae.…”
Section: Resultsmentioning
confidence: 99%
“…albopictus is the most common species found in tires in the southeast (Yee 2008). Eggs are laid singly above the water line or, in limited instances, directly on the water surface (Hawley 1988, Rey andO'Connell 2014). This former habit takes advantage of future environmental conditions, as eggs won't hatch until a precipitation event has occurred and rising water levels cover the eggs, thus maximizing the time for larval development.…”
Section: Nutrient Environmentsmentioning
confidence: 99%